Comparison of Glutathione Nanoparticles, CoEnzyme Q10, and Fish Oil for Prevention of Oxygen-Induced Retinopathy in Neonatal Rats - Sidra Bashir; Charles L. Cai; Matthew Marcelino; Jacob V. Aranda; Kay D. Beharry (MDPI AG, 2024)
Notch ligands and receptors are important for cell specification and angiogenesis, but their role in oxygen-induced retinopathy (OIR) is not well studied. Delta-like ligand (DLL)-4/Notch inhibits angiogenesis, while Jagged-1/Notch promotes angiogenesis. We tested the hypothesis that early supplementation with antioxidants and/or fish oil curtails severe OIR by inducing DLL-4/Notch and reducing Jagged-1/Notch. Newborn rats were exposed to brief intermittent hypoxia (IH) during hyperoxia, during which they received daily oral supplements of (1) fish oil, (2) coenzyme Q10 (CoQ10) in olive oil (OO), (3) glutathione nanoparticles (nGSH), (4) fish oil + CoQ10, or (5) OO (controls) from birth (P0) to P14. At P14, the pups were placed in room air (RA) until P21, with no further treatment. Oxidative stress, apoptosis, ocular histopathology, and Notch signaling were assessed. Neonatal IH resulted in severe retinal damage consistent with retinopathy of prematurity (ROP). Retinal damage was associated with induced oxidative stress and Jagged-1/Notch signaling, as well as reduced DLL-4/Notch signaling. All treatments reversed these outcomes, but nGSH produced the most beneficial outcomes. Severe OIR promoted the induction of Jagged-1/Notch and curtailed DLL-4/Notch, which was an effect that could be reversed with nGSH supplementation. These findings may indicate a potential alternate pathway for ROP treatment and/or prevention.